2007
DOI: 10.1101/gad.450107
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin induces immortalization of melanocytes by suppressing p16INK4a expression and cooperates with N-Ras in melanoma development

Abstract: Tumor progression is a multistep process in which proproliferation mutations must be accompanied by suppression of senescence. In melanoma, proproliferative signals are provided by activating mutations in NRAS and BRAF, whereas senescence is bypassed by inactivation of the p16 Ink4a gene. Melanomas also frequently exhibit constitutive activation of the Wnt/␤-catenin pathway that is presumed to induce proliferation, as it does in carcinomas. We show here that, contrary to expectations, stabilized ␤-catenin redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
281
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(300 citation statements)
references
References 60 publications
14
281
0
5
Order By: Relevance
“…Many human melanomas exhibit activated Wnt signaling (18,24,25), and Larue and coworkers previously showed that a stabilized β-catenin allele drives escape from N-RAS Q61K -induced senescence and ultimately progression to melanoma (18). To date, we have not observed melanoma in any of our Tyr-Cre APC fl.fl /Tyr-N-RAS Q61K mice.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Many human melanomas exhibit activated Wnt signaling (18,24,25), and Larue and coworkers previously showed that a stabilized β-catenin allele drives escape from N-RAS Q61K -induced senescence and ultimately progression to melanoma (18). To date, we have not observed melanoma in any of our Tyr-Cre APC fl.fl /Tyr-N-RAS Q61K mice.…”
Section: Discussionmentioning
confidence: 60%
“…Moreover, Larue and coworkers (18) demonstrated that activation of Wnt signaling in mouse melanocytes is able to bypass senescence by β-catenin-mediated repression of the tumor suppressor, p16. Here we have further analyzed the regulation and function of Wnt signaling in senescent human melanocytes in vitro, in human tissues, and in a mouse model.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Finally, TCF-bcat can also directly repress transcription (Hoverter and Waterman 2008); targets include decapentaplegic in fly imaginal discs (Theisen et al 2007), E-cadherin in mouse keratinocytes (Jamora et al 2003), and p16INK4a in melanomas (Delmas et al 2007). In these cases, TCF acts through traditional sites, but TCF-Arm repression of Ugt36Bc in fly hemocytes occurs through highly divergent sites .…”
Section: Into the Nucleus-target Gene Regulation By Bcat/armmentioning
confidence: 99%
“…After BRAF , which harbors an activating mutation in 40% to 50% of cutaneous melanomas, NRAS is mutated in approximately 20% of tumors ( 1,2 ). Although a mouse model of melanoma driven by expression of BRAF V600E in the absence of other mutations has been developed, current NRAS-driven models rely on concomitant mutations in tumor suppressor genes (3)(4)(5). In this issue of Cancer Discovery , Pedersen and colleagues ( 6 ) show that melanocytic expression of activated NRAS results in melanoma of a quite unexpected type.…”
mentioning
confidence: 99%